Logarithmic Proof (23/03/2015)

Prove that:

\ln { \left( xy \right)  } =\ln { x+\ln { y }  }

Now, say that:

{ a }^{ m }=x\\ \\ \therefore \quad \log _{ a }{ x=m } \\ \\ { a }^{ q }=y\\ \\ \therefore \quad \log _{ a }{ y } =q

So…

LHS\\ \\ =\ln { \left( { a }^{ m }\cdot { a }^{ q } \right)  } \\ \\ =\ln { \left( { a }^{ \left( m+q \right)  } \right)  } \\ \\ =\left( m+q \right) \cdot \ln { a } \\ \\ =\left( \log _{ a }{ x } +\log _{ a }{ y }  \right) \cdot \log _{ e }{ a } \\ \\ =\frac { \log _{ a }{ x } +\log _{ a }{ y }  }{ \log _{ a }{ e }  } \\ \\ =\frac { \log _{ a }{ x }  }{ \log _{ a }{ e }  } +\frac { \log _{ a }{ y }  }{ \log _{ a }{ e }  } \\ \\ =\log _{ e }{ x } +\log _{ e }{ y } \\ \\ =\ln { x } +\ln { y } \\ \\ =RHS

Other posts you may be interested in...